Development of human health ambient water quality criteria of 12 polycyclic aromatic hydrocarbons (PAH) and risk assessment in China. (August 2020) - Chen, Jin; Fan, Bo; Li, Ji; Wang, Xiaonan; Li, Wenwen; Cui, Liang; Liu, Zhengtao
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widely distributed in various environmental media and have thus attracted extensive attention worldwide. To prevent and control PAH pollution in China, the study of ambient water quality criteria (AWQC), human health risks, and aquatic ecological risk is critical. There are no reports to date on the human health AWQC of PAHs in China. Therefore, this study first derived the human health AWQC values of 12 PAHs based on exposure data and bioaccumulation factor in China. We found that local exposure parameters and other relevant factors were key during the development of AWQC in different countries and regions, which led to differences with the reference value recommended by USEPA. Based on the incremental life time cancer risk (ILCR), hazard quotients (HQ) and potentially affected fraction (PAF) methods, the health and ecological risks of 16 PAHs were assessed subsequently. And the results are as follows: the non-carcinogenic PAHs' health risks ranged from 1.01 × 10 −10 to 1.60 × 10 −9, and carcinogenic PAH health risks ranged from 5.03 × 10 −7 to 4.74 × 10 −5 . The toxic effects of 8 PAHs on aquatic organisms exhibited the following order: benzo (a) pyrene (BaP) > anthracene (Ant) > pyrene (Pye) > phenanthrene (Phe) > fluoranthene (Flua) > acenaphthene (Ace) > fluorene (Flu) > naphthalene (Nap). Among these, the ecological risks posed by Ant and BaP were the highest, according to the HQ and PAF methods. Highlights: The first derivation of Chinese WQC for the protection of human health for PAHs. Carcinogenic and noncarcinogenic PAHs' health risk was analyzed in seven river basins. Ecological risk assessment of PAHs was conducted in seven river basins in China.